2010
DOI: 10.2147/lra.s8600
|View full text |Cite
|
Sign up to set email alerts
|

Femoral nerve block versus fentanyl: Analgesia for positioning patients with fractured femur

Abstract: PurposeFracture of femur is a painful bone injury, worsened by any movement. This prospective study was performed to compare the analgesic effects of femoral nerve block (FNB) with intravenous (IV) fentanyl prior to positioning patients with fractured femur for spinal block.Patients and methodsSixty-four ASA I–III patients aged 18–80 years undergoing surgery for femur fracture were randomized into two groups. Fifteen minutes before spinal block, the FNB group received nerve stimulator-assisted FNB with a mixtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 19 publications
3
57
1
Order By: Relevance
“…Full-text articles were excluded with no comparison (n = 4), no comparison of interest (n = 6), different interventions (n = 9), no relevant outcome measure (n = 12), and review articles (n = 4). Ten studies [10][11][12][13][14][15][16][17][18][19] were ultimately included for qualitative and quantitative synthesis. single centers in Italy [16], Ireland [18], Pakistan [10], India [12,13,15,17,19], Nepal [14], and Thailand [11].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Full-text articles were excluded with no comparison (n = 4), no comparison of interest (n = 6), different interventions (n = 9), no relevant outcome measure (n = 12), and review articles (n = 4). Ten studies [10][11][12][13][14][15][16][17][18][19] were ultimately included for qualitative and quantitative synthesis. single centers in Italy [16], Ireland [18], Pakistan [10], India [12,13,15,17,19], Nepal [14], and Thailand [11].…”
Section: Discussionmentioning
confidence: 99%
“…Two [10,12] of the studies recruited a majority of females for FNB. Four [11,15,17,19] studies recruited equal numbers of the two sexes, and one [13] study provided no information on sex. Three trials [10,11,16] reported the time from trauma to surgery, and averages ranged from 2.3-15.6 days.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is sufficient data to show the usefulness of FNB to relieve pain from fracture of the femur and now, is being used for positioning during central neuraxial blockade as well. 3,4,12,[19][20][21][22] Femoral nerve block can be performed using peripheral nerve stimulator, ultrasound guided technique or by loss of resistance technique. Geier KO concluded that there were no significant differences regarding efficiency between loss of resistance and peripheral nerve stimulator methods.…”
mentioning
confidence: 99%